1974
DOI: 10.1161/01.cir.50.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Predictors of Myocardial Oxygen Consumption During Static and Dynamic Exercise

Abstract: Hemodynamic predictors of myocardial oxygen consumption (MVO 2 ) during static and dynamic exercise were examined in ten normal subjects. Studies were done under the following circumstances: 1) during upright bicycle exercise at an average heart rate of 147 beats/min, 2) during static exercise with an isometric load in the left hand equal to 17% of the maximal voluntary contraction (MVC), and 3) during combined dynamic exercise (average heart rate 147 beats/min) and static exercise usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
175
5

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(193 citation statements)
references
References 56 publications
13
175
5
Order By: Relevance
“…We noticed that either positive or negative stimulation of the beta-adrenergic receptor led to a decrease in mean systemic blood pressure, although with dobutamine, this effect did not reach statistical significance (p = 0.08). Nevertheless, the RPP, which is known to be well correlated with the oxygen consumption [23], was found to hold true even when the blood pressure was decreased through pharmacological manipulation. In the current study, we were therefore able to confirm the relationship between the RPP and myocardial oxygen consumption.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We noticed that either positive or negative stimulation of the beta-adrenergic receptor led to a decrease in mean systemic blood pressure, although with dobutamine, this effect did not reach statistical significance (p = 0.08). Nevertheless, the RPP, which is known to be well correlated with the oxygen consumption [23], was found to hold true even when the blood pressure was decreased through pharmacological manipulation. In the current study, we were therefore able to confirm the relationship between the RPP and myocardial oxygen consumption.…”
Section: Discussionmentioning
confidence: 94%
“…Among the various parameters that have been proposed to measure the oxygen demand in healthy subjects [8], the heart rate-pressure product (RPP) (heart rate × systolic pressure) is recognized to be a good index of MVO 2 [8,[21][22][23]. In the validation experiment, we were able to calculate the RPP using the heart rate and the measurements of the systolic pressure obtained with the arterial pressure analyzer.…”
Section: Correlation Of the Index Of Myocardial Oxygen Consumptionmentioning
confidence: 99%
“…20) Hornsten and Bruce 20) demonstrated that 74% of the total variation in HR was at the first stage of exercise in AF patients. Other studies 8,[17][18][19][20] have found that the increase in HR was maximal at the lowest stage of workload (for example: at 3.0 mph, 0% grade, and under anaerobic conditions) compared to the values at rest; and that less of an increase in HR compared to the first increase occurred at the maximal stage. Therefore, they reported that exercise tests can be used to evaluate the activities of pharmacologic agents for controlling HR in AF patients.…”
Section: Resultsmentioning
confidence: 92%
“…HR increases directly proportional to oxygen uptake and the applied workload. 3) It has been reported that a rapid ventricle response beyond normal was seen at the first stage of static exercise in AF patients 8,[17][18][19] and that this response was higher than in normal subjects. 20) Hornsten and Bruce 20) demonstrated that 74% of the total variation in HR was at the first stage of exercise in AF patients.…”
Section: Resultsmentioning
confidence: 97%
“…Neither the extent of STsegment depression nor the attainment of a target heart rate was used as an end point. Maximal voluntary contraction (MVC) for handgrip was determined in the right hand using a Jaymar hand dynamometer 15 mCi of technetium-99m labeled to human serum albumin was injected 2 hours later.…”
Section: Patient Testing Protocol (Fig 1) Visit 1 -Pretestmentioning
confidence: 99%